Androgens are differentially associated with ovarian cancer subtypes in the Ovarian Cancer Cohort Consortium - Ose, J; Poole, E; Schock, H; Lehtinen, M; Arslan, A; Zeleniuch-Jacquotte, A; Visvanathan, K; Helzlsouer, K; Buring, J; Lee, I; Tjønneland, A; Dossus, L; et al. (American Association for Cancer Research, 2017)
Invasive epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy. The etiology of EOC remains elusive; however, experimental and epidemiologic data suggest a role for hormone-related exposures in ovarian carcinogenesis and risk factor differences by histologic phenotypes and developmental pathways. Research on pre-diagnosis androgen concentrations and EOC risk has yielded inconclusive results, and analyses incorporating EOC subtypes are sparse. We conducted a pooled analysis of 7 nested case-control studies in the Ovarian Cancer Cohort Consortium to investigate the association between pre-diagnosis circulating androgens (testosterone, free testosterone, androstenedione, dehydroepiandrosterone sulfate (DHEAS)), sex hormone binding globulin (SHBG), and EOC risk by tumor characteristics (i.e. histology, grade, and stage). The final study population included 1,331 EOC cases and 3,017 matched controls. Multivariable conditional logistic regression was used to assess risk associations in pooled individual data. Testosterone was positively associated with EOC risk (all subtypes combined, Odds Ratio (OR)log2=1.12 [95% Confidence Interval (CI) 1.02-1.24]); other endogenous androgens and SHBG were not associated with overall risk. Higher concentrations of testosterone and androstenedione associated with an increased risk in endometrioid and mucinous tumors (e.g., testosterone, endometrioid tumors, ORlog2=1.40 [1.03-1.91]), but not serous or clear cell. An inverse association was observed between androstenedione and high grade serous tumors (ORlog2=0.76 [0.60-0.96]). Our analyses provide further evidence for a role of hormone-related pathways in EOC risk, with differences in associations between androgens and histologic subtypes of EOC.